Static and dynamic analyses of stiffened folded laminate composite plate - Thinh, Tran Ich; Binh, Bui Van; Tu, Tran Minh (Vietnam Journal of Mechanics, 2013)
This paper presents some numerical results of bending and vibration analyses of an unstiffened and stiffened folded laminate composite plate using finite element method. The effects of fiber orientations, boundary conditions, stiffener conditions of the plates for deflections, natural frequencies, and the corresponding mode shapes, transient displacement responses were considered. The Matlab programming using rectangular isoparametric plate element with five degree of freedom per node based on Mindlin plate theory was built to solve the problems. A good agreement is found between the results of this technique and other published results available in the literature.